Microstructure development and photoluminescence of annealed nanosized Ce:YAG/Al2O3 and Ce:YAG/Cr:Al2O3 powder composites. (28th March 2018) - Peter, Samuel; Kuyanov, Paul; Goktas, Nebile Isik; LaPierre, Ray; Kitai, Adrian
Abstract: In an effort to control aggregation and sintering of phosphor nanoparticles at elevated annealing temperatures, glycothermally synthesized cerium-doped yttrium aluminum garnet (Ce:YAG) nanoparticles were annealed in a matrix of aluminum oxide between 1000 °C and 1200 °C. Scanning electron microscopy images showed that glycothermal synthesis yields ∼100 nm particles, and that the alumina matrix was able to control grain growth of Ce:YAG at annealing temperatures up to 1200 °C. Analysis by x-ray diffraction and Fourier transform infrared spectroscopy showed an increase in the degree of crystallinity at increasing temperatures as well as the evolution of alumina phases. Photoluminescence of the composite product showed the expected broad Ce:YAG spectrum, with characteristic chromium R lines present due to the formation of corundum at 1200 °C with trace chromium content. The same procedure was performed to synthesize a Ce:YAG/Cr:Al2 O3 nanocomposite, yielding photoluminescence of both the expected Ce:YAG and Cr:Al2 O3 peaks as well as clear evidence of energy transfer between Ce and Cr centers in YAG. The luminescence of these composites was used to determine their CIE colour co-ordinates. It was found that the colour profile of the resulting emission may be tuned by adjusting the Cr content and annealing conditions of the composite materials.